Electric fields accelerate cell polarization and bypass myosin action in motility initiation. Issue 3 (25th August 2017) - Sun, Yao‐Hui; Sun, Yuxin; Zhu, Kan; Reid, Brian; Gao, Xing; Draper, Bruce W.; Zhao, Min; Mogilner, Alex
Abstract : Stationary symmetrical fish keratocyte cells break symmetry and become motile spontaneously but slowly. We found that applying electric field (EF) accelerates the polarization by an order of magnitude. While spontaneously polarized cells move persistently for hours, the EF‐induced polarity is lost in a majority of cells when the EF is switched off. However, if the EF is applied for a long time and then switched off, the majority of cell move stably. Myosin inhibition abolishes spontaneous polarization, but does not slow down EF‐induced polarization, and after the EF is turned off, motility does not stop; however, the cell movements are erratic. Our results suggest that the EF rapidly polarizes the cells, but that resulting polarization becomes stable slowly, and that the EF bypasses the requirement for myosin action in motility initiation. Abstract : Electric field rapidly polarizes fish keratocyte cells, but the resulting polarization becomes stable slowly. Electric field bypasses the requirement for myosin action in motility initiation.